Thermodynamic mechanism for inhibition of lactose permease by the phosphotransferase protein IIA Glc - Hariharan, Parameswaran; Balasubramaniam, Dhandayuthapani; Peterkofsky, Alan; Kaback, H. Ronald; Guan, Lan (Proceedings of the National Academy of Sciences - PNAS, 2015)
Carbohydrate uptake in many bacteria is regulated by the phosphotransferase protein IIA Glc , enabling cells to use glucose preferentially over other sugars. Lactose permease (LacY) is one of many sugar permeases regulated by IIA Glc , but the mechanism of inducer exclusion is unclear. We now show by isothermal titration calorimetry that IIA Glc binds to purified LacY with a stoichiometry of one, and that the interaction is driven by favorable solvation entropy. IIA Glc binding inhibits conformational dynamics of LacY and decreases binding affinity for sugar in a manner similar to that observed for melibiose permease (MelB). However, the thermodynamic mechanism by which the inhibitory effect is expressed differs for the two permeases. In a variety of bacteria, the phosphotransferase protein IIA Glc plays a key regulatory role in catabolite repression in addition to its role in the vectorial phosphorylation of glucose catalyzed by the phosphoenolpyruvate:carbohydrate phosphotransferase system (PTS). The lactose permease (LacY) of Escherichia coli catalyzes stoichiometric symport of a galactoside with an H + , using a mechanism in which sugar- and H + -binding sites become alternatively accessible to either side of the membrane. Both the expression (via regulation of cAMP levels) and the activity of LacY are subject to regulation by IIA Glc (inducer exclusion). Here we report the thermodynamic features of the IIA Glc –LacY interaction as measured by isothermal titration calorimetry (ITC). The studies show that IIA Glc binds to LacY with a K d of about 5 μM and a stoichiometry of unity and that binding is driven by solvation entropy and opposed by enthalpy. Upon IIA Glc binding, the conformational entropy of LacY is restrained, which leads to a significant decrease in sugar affinity. By suppressing conformational dynamics, IIA Glc blocks inducer entry into cells and favors constitutive glucose uptake and utilization. Furthermore, the studies support the notion that sugar binding involves an induced-fit mechanism that is inhibited by IIA Glc binding. The precise mechanism of the inhibition of LacY by IIA Glc elucidated by ITC differs from the inhibition of melibiose permease (MelB), supporting the idea that permeases can differ in their thermodynamic response to binding IIA Glc .